Femtosecond laser direct writing in SiO2‐Al2O3 binary glasses and thermal stability of Type II permanent modifications. Issue 8 (7th May 2020) - Wang, Yitao; Wei, Shuen; Cicconi, Miss R.; Tsuji, Yuta; Shimizu, Masahiro; Shimotsuma, Yasuhiko; Miura, Kiyotaka; Peng, Gang‐Ding; Neuville, Daniel R.; Poumellec, Bertrand; Lancry, Matthieu
Abstract: We investigate the potential of fabricating thermally stable refractive index contrasts using femtosecond (fs) near‐infrared (IR) radiation in aluminosilicate glasses. A set of pure SiO2 ‐Al2 O3 glasses are manufactured, characterized (density and Raman), and investigated after being irradiated by fs laser within the Type II regime. The formation of nanogratings is identified and studied using quantitative birefringence measurements. Their thermal stability is then investigated through 30 minutes step isochronal annealing (up to 1250°C). For both SiO2 and 50SiO2 ‐50Al2 O3 compositions, the normalized birefringence does not decrease when tested up to 1100°C, while for the 4, 6 mol% GeO2 ‐SiO2 erased for 20% at 1000°C.